DYNAMICAL BEHAVIOUR OF THE JOSEPH-EGRI EQUATION - Sabi'u, Jamilu; İnç, Mustafa; Leta, Temesgen D.; Baleanu, Dumitru; Rezazade, Hadi (Vinca Inst Nuclear Sci, 2023)
We investigate traveling wave solutions to the Joseph-Egri equation via extended auxiliary equation technique. We have determined stationary points of the dynamical systems by using bifurcation method. We also acquire cusp, periodic and homoclinic orbits. The investigated solutions are entirely different from the reported in the liter-ature. However, some of the reported solutions are plotted to understand the physical application of the considered model using renowned mathematical software.
Keywords: Joseph-Egri equation; extended auxiliary equation technique; soliton solutions